2022
DOI: 10.1039/d2ce00362g
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of surface kinetics: rapid growth of n-AlGaN with high conductivity for deep-ultraviolet light emitters

Abstract: A rapid growth strategy for n-AlGaN with fine electrical properties has been put forward aiming at deep-ultraviolet light emitters. By shortening the terrace width using sapphire with large miscut angles,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…The reduction in surface undulation with the miscut angle of MRSS increased from 0°to 0.5°was attributed to the inhibition of the three-dimensional (3D) growth mode by additional lateral nucleation on the narrow step formed on the MRSS with a small miscut angle of 0.5°. 20 However, both the step width and height of the a-plane GaN film increased as the miscut angle of the MRSS was further increased from 0.5°to 2.0°. Meanwhile, small triangular pits located at the ends of the stripes were also evident and were generated due to the slow epitaxial growth rate along the [0001 ¯] direction.…”
Section: Resultsmentioning
confidence: 96%
“…The reduction in surface undulation with the miscut angle of MRSS increased from 0°to 0.5°was attributed to the inhibition of the three-dimensional (3D) growth mode by additional lateral nucleation on the narrow step formed on the MRSS with a small miscut angle of 0.5°. 20 However, both the step width and height of the a-plane GaN film increased as the miscut angle of the MRSS was further increased from 0.5°to 2.0°. Meanwhile, small triangular pits located at the ends of the stripes were also evident and were generated due to the slow epitaxial growth rate along the [0001 ¯] direction.…”
Section: Resultsmentioning
confidence: 96%
“…It is worth noting that although the relatively low growth temperature (lower than 1050 °C) is beneficial to the electrical property, it is unfavorable for the two-dimensional growth of Al-rich AlGaN, hence resulting in the rough surface morphology. Studies at Peking University indicated that the upper-bound growth rate for the smooth surface of n-Al 0.65 Ga 0.35 N is around 0.65 μm/h at 1100 °C on conventional sapphire with a miscut angle of 0.2° [ 57] . It is convinced that the critical rate would further decrease at a lower temperature to pursue better electrical properties in n-AlGaN.…”
Section: N-algan With Al Composition Lower Than 80%mentioning
confidence: 99%
“…Besides, the limited effective doping concentration and surface etching damage in Al-rich n-AlGaN have posed significant challenges to implementing ohmic contact and low resistance even through high-temperature annealing. , Furthermore, the upper-bound growth rate for the two-dimensional growth of Al-rich n-AlGaN is experimentally determined to be around 0.65 μmh –1 at 1100 °C . Also, it can be expected that the critical rate will further decrease at a lower temperature . As such, the growth of thick n-AlGaN (1.5–3.5 μm) occupies quite a large part of the total growth time of a conventional DUV-LED structure.…”
Section: Introductionmentioning
confidence: 99%
“…22 Also, it can be expected that the critical rate will further decrease at a lower temperature. 23 As such, the growth of thick n-AlGaN (1.5−3.5 μm) occupies quite a large part of the total growth time of a conventional DUV-LED structure. In this work, to reduce or even eliminate the negative impact of dislocation defects in n-AlGaN on the active region, we propose a n-AlGaN free transverse structure LED for the first time.…”
Section: ■ Introductionmentioning
confidence: 99%